Development of a level 5 autonomous car on a 1/10 scale RC car platform - Hegazy, A. M. (Инноватика-2025 : сборник материалов XXI Международной школы-конференции студентов, аспирантов и молодых ученых, 28-30 апреля 2025 г., г. Томск, Россия)
This article shows the possibility of building a level 5 full autonomous car on a scale 1/10 RC car platform. That is capable of navigation through track, by using localization, mapping and vision techniques and with a minimum cost.